Sentimental Analysis on Product Reviews - B Ramya Sree , Potlapally Sai Vivek , Ram Gopal Adapa , Y Harika Devi , Manthena Prudhvi Raju , V Divyavani (International Journal of Advanced Science and Technology, 2020)
A Sentiment could be a read of perspective towards a scenario or an event thus forming an opinion. Sentimental Analysis fundamentally is nothing but an opinion extraction. The term Sentimental analysis is used to distinguish the two different concepts one being extracting and knowing the Sentiments being expressed in documents in text, whereas the other being the task of allocating class labels to the text in the documents. In this project my goal is to analyses the text reviews from an online source and convert useful data into a point matrix, then perform the desired analysis on the data thus obtained.